Representing moisture fluxes and phase changes in glacier debris cover using a reservoir approach - Collier, Emily; Nicholson, Lindsey; Brock, Benjamin; Maussion, Fabien; Essery, Richard; Bush, Andrew (The Cryosphere, 2014)
Due to the complexity of treating moisture in supraglacial debris, surface energy balance models to date have neglected moisture infiltration and phase changes in the debris layer. The latent heat flux (QL) is also often excluded due to the uncertainty in determining the surface vapour pressure. To quantify the importance of moisture on the surface energy and climatic mass balance (CMB) of debris-covered glaciers, we developed a simple reservoir parameterization for the debris ice and water content, as well as an estimation of the latent heat flux. The parameterization was incorporated into a CMB model adapted for debris-covered glaciers. We present the results of two point simulations, using both our new “moist” and the conventional “dry” approaches, on the Miage Glacier, Italy, during summer 2008 and fall 2011. The former year coincides with available in situ glaciological and meteorological measurements, including the first eddy-covariance measurements of the turbulent fluxes over supraglacial debris, while the latter contains two refreeze events that permit evaluation of the influence of phase changes. The simulations demonstrate a clear influence of moisture on the glacier energy and mass-balance dynamics. When water and ice are considered, heat transmission to the underlying glacier ice is lower, as the effective thermal diffusivity of the saturated debris layers is reduced by increases in both the density and the specific heat capacity of the layers. In combination with surface heat extraction by QL, subdebris ice melt is reduced by 3.1% in 2008 and by 7.0% in 2011 when moisture effects are included. However, the influence of the parameterization on the total accumulated mass balance varies seasonally. In summer 2008, mass loss due to surface vapour fluxes more than compensates for the reduction in ice melt, such that the total ablation increases by 4.0 %. Conversely, in fall 2011, the modulation of basal debris temperature by debris ice results in a decrease in total ablation of 2.1 %. Although the ...